Influencia en el ambiente de los residuos obtenidos en el proceso de aserrío de diferentes especies en la empresa Forestal Requena Maynas - Iquitos – 2022 - Reguera Tapullima, Pedro Junior (2023)
The present study was carried out in the wood transformation plant of the FORESTAL REQUENA company, locate on Santa María-Iquitos-Loreto highway, in order to determine the influence on the environment of the residues obtained in the sawmill process of different species in the company. According to the results, it is found that the vast majority of workers are of a low socio.economic level, being between categories D and E. The average volumen of raw wood for the sawmill is 41.35 m3, from which a yield of 28.71 m³ is obtained, equivalent in percentage terms to 72.35%, with the average daily waste of 12.63 m³ reaching 27.65%. The production of waste and residues reaches 3261.12 m³/year. The solid waste with the greatest presence is the bark of the different species, sawdust and shavings, which generate considerable levels of contamination inside and outside the facilities. The average solid waste generation generated by the company is 3261.12 m³/year. The use given to solid waste is 10% for domestic use, 10% for farms, 5 for others uses and 75% for our consumption. Liquid waste such as water, oil and Grease are dumped within the sawmill area, generating low levels of contamination. The noise genarated inside the facilities is 89.6 dB maximum and 75.69 dB minimum, while outside the facilities it reaches a maximum of 63.95 dB and a minimum of 61.69 bB the WHO.